2000
DOI: 10.1007/s002449910013
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Exposure and Biomarker Responses in Spectacled Eiders ( Somateria fischeri ) from St. Lawrence Island, Alaska

Abstract: Effects of chemical contaminant exposure may be contributing to the decline of spectacled eiders (Somateria fischeri) nesting in coastal areas of western Alaska. We evaluated chemical exposure and potential effects in 20 male eiders collected near St. Lawrence Island, Alaska. Analytes included metals, trace elements, chlorinated organics, and (137)Cesium ((137)Cs). Effects of contaminant exposure were evaluated using histopathology and biochemical measures of porphyrin profiles, cytochrome P450 activities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 27 publications
8
38
2
Order By: Relevance
“…This is in accordance with the observations made by Elliott et al (1992) who did not find any indications of renal MT concentrations leveling off in seabirds even at very high Cd tissue levels. A cautious comparison with earlier studies (standardized to ww) does suggest that MT concentrations in ptarmigan observed in this study were in the high end of values reported earlier (Elliott et al 1992;Trust et al 2000;Barjaktarovic et al 2002). The general picture for different species would be that MT concentration to a large extent reflect tissue metal levels, so that low MT levels are found in species with low metal levels, e.g., scoters (Melanitta spp.…”
Section: Metals and Mt Content In Tissuesmentioning
confidence: 47%
See 1 more Smart Citation
“…This is in accordance with the observations made by Elliott et al (1992) who did not find any indications of renal MT concentrations leveling off in seabirds even at very high Cd tissue levels. A cautious comparison with earlier studies (standardized to ww) does suggest that MT concentrations in ptarmigan observed in this study were in the high end of values reported earlier (Elliott et al 1992;Trust et al 2000;Barjaktarovic et al 2002). The general picture for different species would be that MT concentration to a large extent reflect tissue metal levels, so that low MT levels are found in species with low metal levels, e.g., scoters (Melanitta spp.…”
Section: Metals and Mt Content In Tissuesmentioning
confidence: 47%
“…The structure, evolution, and properties of avian MT were reviewed by Andrews et al (1996). However, studies of MT in free-living birds are scarce and have so far been limited to studies in aquatic bird species (e.g., Elliott et al 1992;Bouquegneau et al 1996;Elliott and Scheuhammer 1997;Trust et al 2000;Nam et al 2005) and tree swallows (Tachycineta bicolour) (Louis et al 1993), whereas galliformes were only studied under laboratory conditions (e.g., Scheuhammer 1988;Shartzer et al 1993). In mammals and birds, Cd accumulates to high levels in kidney, and a threshold for renal toxicity in birds was suggested to be around 100 mg/kg wet weight (ww) (e.g., Furness 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were screened for 19 elements at the Research Triangle Institute (Research Triangle Park, North Carolina, USA) using analytical procedures similar to those described by Trust et al (2000). Arsenic and selenium levels were determined using graphite furnace atomic absorption spectrometry analysis; mercury levels were determined using cold vapor atomic absorption analysis, and all other elements were determined using inductively-coupled plasma emission spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Its presence in numerous environments is due to its widespread industrial use. For instance, in Alaska, very high levels of cadmium were reported in kidneys of Spectacled eiders (Somateria fischeri) (Trust et al 2000). These levels can lead to various effects on organisms such as the induction of inflammation of renal interstitium and marked degenerative changes in testes (Hughes et al 2000).…”
Section: Introductionmentioning
confidence: 98%